Free and universal access to primary healthcare in Mongolia: the service availability and readiness assessment - Altantuya Jigjidsuren; Tumurbat Byambaa; Enkhjargal Altangerel; Suvd Batbaatar; Yu Mon Saw; Tetsuyoshi Kariya; Eiko Yamamoto; Nobuyuki Hamajima (BMC, 2019)
Abstract Background The government of Mongolia mandates free access to primary healthcare (PHC) for its citizens. However, no evidence is available on the physical presence of PHC services within health facilities. Thus, the present study assessed the capacity of health facilities to provide basic services, at minimum standards, using a World Health Organization (WHO) standardized assessment tool. Methods The service availability and readiness assessment (SARA) tool was used, which comprised a set of indicators for defining whether a health facility meets the required conditions for providing basic or specific services. The study examined all 146 health facilities in Chingeltei and Khan-Uul districts of Ulaanbaatar city, including private and public hospitals, family health centers (FHCs), outpatient clinics, and sanatoriums. The assessment questionnaire was modified to the country context, and data were collected through interviews and direct observations. Data were analyzed using SPSS 21.0, and relevant nonparametric tests were used to compare median parameters. Results A general service readiness index, or the capacity of health facilities to provide basic services at minimum standards, was 44.1% overall and 36.3, 61.5, and 62.4% for private clinics, FHCs, and hospitals, respectively. Major deficiencies were found in diagnostic capacity, supply of essential medicines, and availability of basic equipment; the mean scores for general service readiness was 13.9, 14.5 and 47.2%, respectively. Availability of selected PHC services was 19.8%. FHCs were evaluated as best capable (69.5%) to provide PHC among all health facilities reviewed (p < 0.001). Contribution of private clinics and sanatoriums to PHC service provisions were minimal (4.1 and 0.5%, respectively). Service-specific readiness among FHCs for family planning services was 44.0%, routine immunization was 83.6%, antenatal care was 56.5%, preventive and curative care for children was 44.5%, adolescent health services was 74.2%, tuberculosis services was 53.4%, HIV and STI services was 52.2%, and non-communicable disease services was 51.7%. Conclusions Universal access to PHC is stipulated throughout various policies in Mongolia; however, the present results revealed that availability of PHC services within health facilities is very low. FHCs contribute most to providing PHC, but readiness is mostly hampered by a lack of diagnostic capacity and essential medicines.